2019
DOI: 10.3389/fendo.2019.00089
|View full text |Cite
|
Sign up to set email alerts
|

When RON MET TAM in Mesothelioma: All Druggable for One, and One Drug for All?

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive inflammatory cancer with a poor survival rate. Treatment options are limited at best and drug resistance is common. Thus, there is an urgent need to identify novel therapeutic targets in this disease in order to improve patient outcomes and survival times. MST1R (RON) is a trans-membrane receptor tyrosine kinase (RTK), which is part of the c-MET proto-oncogene family. The only ligand recognized to bind MST1R (RON) is Macrophage Stimulating 1 (MST1), also kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Met-5A is a human mesothelial cell line immortalized by the transformation of epithelial virus SV40. Met-5A expresses a high level of AXL RNA [31]. To the best of our knowledge, we described for the first time here a LAMP assay for detection of AXL in complex biological samples.…”
Section: Resultsmentioning
confidence: 99%
“…Met-5A is a human mesothelial cell line immortalized by the transformation of epithelial virus SV40. Met-5A expresses a high level of AXL RNA [31]. To the best of our knowledge, we described for the first time here a LAMP assay for detection of AXL in complex biological samples.…”
Section: Resultsmentioning
confidence: 99%
“…Met-5A is a human mesothelial cell line immortalized by the transformation of epithelial virus SV40. Met-5A expresses a high level of AXL RNA [ 31 ]. To the best of our knowledge, we described for the first time, here, a LAMP assay for the detection of AXL in complex biological samples.…”
Section: Resultsmentioning
confidence: 99%
“…A pharmacological approach using a small molecule RON inhibitor was employed to determine if blocking RON ligand, MSP‐induced RON receptor activation (tyrosine phosphorylation in the kinase domain) inhibits HIF‐1 α expression and invasive behavior of PDAC cells. LCRF, a small molecule RON TKI was recently reported to block MSP/RON signaling and inhibit the growth of malignant pleural mesothelioma 41 . To determine if LCRF is effective in blocking RON phosphorylation and activation in PDAC cells, we initially carried out an LCRF dose–response analysis and determined 400 nM dosage was effective in blocking RON ligand, MSP‐induced phosphorylation of RON tyrosine kinase receptor.…”
Section: Resultsmentioning
confidence: 99%
“…As RON has been documented to be involved in the development and progression of various tumor types, 13 preclinical/clinical efforts are being aggressively pursued to develop small molecule or antibody‐drug conjugate therapies 15–17 . Recently, a small molecule RON inhibitor, LCRF was reported to block MSP/RON signaling and inhibited the growth of malignant pleural mesothelioma 41 . Notably, we found that this RON TKI was effective in blocking the MSP/RON signaling pathway induced HIF‐1 α expression in the PDAC cells (Figure 3A).…”
Section: Discussionmentioning
confidence: 99%